PENGENDALIAN BAHAN BAKU DENGAN MENGGUNAKAN PENDEKATAN JUST IN TIME DI PT. DHARMALINDO EKA PERSADA - Periyansah, Periyansah; Rahayu, Monita; Arlianti, Lily (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2023)
PT. Dharmalindo Eka Persada, a foam-based producer, is facing the problem of stockpiling raw materials for aluminum thermal insulation and anti-vibration products due to unstable fluctuations in market demand. This study analyzes the application of the just in time method in companies for inventory cost efficiency. Using a qualitative descriptive approach with interviews, library studies, and inventory reports for 2022, the study found that current inventory control policies are not optimal. In the case of the raw material polyurethane foam eow gray, savings of 55% were achieved with the JIT method, reducing inventory costs from Rp.18,553,771 to Rp.8,297,499. For the raw material polyethylene foam fireretendant, savings of 55% also occurred with inventory costs falling from Rp.43,655,932 to Rp.19,523,526.